Expression and Pathogenic Analysis of Integrin Family Genes in Systemic Sclerosis - Xu, Dan; Li, Ting; Wang, Ruikang; Mu, Rong (Frontiers in Medicine, 2021)
Objectives. Emerging evidence shows that integrin members are involved in inflammation and fibrosis in systemic sclerosis (SSc). This study aimed at evaluating the expression of integrin family genes in skin tissue from SSc patients and exploring the potential pathogenic mechanism. Methods. We utilized the public datasets of SSc skin tissue from Gene Expression Omnibus (GEO) database to analyze the expression and clinical significance of integrin family genes in SSc. Expression of integrin members in skin tissue were also assessed by immunohistochemistry. In addition, functional enrichment and pathway analysis were conducted. Results. Compared with healthy controls, the mRNA and protein levels of ITGA5, ITGB2 and ITGB5 were up-regulated in the skin of SSc patients. Further analysis indicated that the mRNA expression levels of ITGA5, ITGB2 and ITGB5 were positively correlated with modified Rodnan skin thickness score (mRSS). Functional enrichment and pathway analysis showed that integrin members may play multiple roles in pathogenesis of SSc. Among them, ITGA5, ITGB2 and ITGB5 might synergistically promote SSc through affecting extracellular matrix (ECM) turn over, ECM-receptor interaction, focal adhesion and leukocyte trans-endothelial migration, while, ITGA5 and ITGB5 also might affect angiogenesis and endothelial cell function. In addition, ITGA5, ITGB2 and ITGA5 were associated with different pathways, respectively. ITGA5 uniquely enriched for actin organization, while ITGB5 for TGF-β signaling and ITGB2 for immune cells activation. Conclusion. Our results implied that the abnormal expression of integrin family genes including ITGA5, ITGB2 and ITGB5 may participate in multiple pathological processes in SSc. Further investigations are required for confirming this speculation.